Dual-band transparent antenna for ISM band applications - Abdul Rani, Mohd. Subri (2013)
A compact dual-band transparent antenna with co-planar waveguide (CPW)-fed for wireless applications in the unlicensed industrial, scientific and medical (ISM) band is proposed in this paper. The proposed antenna generates two bands at 2.4 and 5.8 GHz for Wireless Local Area Network (WLAN) access points and point-to-point applications, respectively. The CPW technique is used to feed the circular radiating element. Two slots line are introduced in the antenna to obtain the desired resonating frequencies. Results and analysis from introduction of the slot lines are highlighted in this paper. The antenna utilizes a conductive silver coated film (AgHT) as the core material as the substrate, making the antenna almost 82% transparent. The proposed antenna is very small, having an overal size of 60 × 60 × 0.175mm3, when compared to other conventional non-transparent antenna operating at the same frequencies of 2.45 and 5.8 GHz. The combination of transparency and small size enables the antenna to be integrated into any flat surface with low chances of being noticed. The antenna can be integrated into the window glass of a building and performs as an access point to provide wireless signal around it. In addition, the antenna can also serve as a tinted film to provide an extra layer of protection from the sun radiation when integrated into the buildings' windows. The integration of the antenna into building windows will reduces the space consumption and remove the space limitation problems faced when using the conventional non-transparent antenna. The proposed prototype antenna has acceptable performances in terms of return loss, gain, efficiency and omni-directional radiation pattern. Simulated and experimental results are discussed. Copyright © 2013 The Electromagnetics Academy.